Prospek Pengembangan Hortikultura (Studi Kasus: Subang, Jawa Barat) - Saridewi, Tri Ratna; Ilhami, Wasissa Titi; Syafaruddin (Politeknik Pertanian Bogor, 2025)
The Government of Subang Regency acknowledges the strategic role of horticultural production in supporting regional development financing. However, the recent decline in pineapple production, which has long been the region’s flagship commodity, highlights the need to identify alternative horticultural products with strong economic potential. This study aims to explore the added value of selected commodities through the development of derivative products that can enhance competitiveness and sustainability. A descriptive approach was employed, using two stages of Focus Group Discussions (FGDs). The first stage served to verify and validate preliminary findings, while the second stage focused on designing development strategies. Twenty respondents participated, representing the Department of Agriculture, agribusiness entrepreneurs, banking institutions, and millennial farmers. The results show that pineapple, mangosteen, and mango are the most promising commodities for agribusiness expansion. Processing these fruits into derivative products reduces the risk of post-harvest losses, extends shelf life, ensures year-round availability, creates new product varieties, and offers potential health and cultural value. These innovations provide higher economic returns, increase farmers’ income, strengthen business sustainability, and diversify market opportunities. To achieve these outcomes, continuous promotion is needed to improve consumer awareness, alongside the development of commercial seed production using certified superior seeds. The findings suggest that value-added horticultural products can significantly enhance the contribution of the agricultural sector to regional economic development in Subang.